2019
DOI: 10.4094/chnr.2019.25.4.477
|View full text |Cite
|
Sign up to set email alerts
|

Structural Equation Model of Health Promotion Behaviors in Late School-aged Children: Based on the Theory of Planned Behavior

Abstract: This study was conducted to investigate the factors affecting health promotion behaviors in late school-aged children by establishing a hypothetical model based on the planned behavior theory. Methods: From July 19 to August 31, 2017, 460 questionnaires were distributed to fifth and sixth graders at three elementary schools in Korea, of which 318 were ultimately analyzed. Results: All the fit indices were shown to be appropriate, indicating satisfactory fit. In the final model, six of the nine paths included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…Wang and Wang (2015) found that intention has a significant effect on children's (ages 9 to 13) physical activity, attitude and perceived behavioral control have a significant effect on intention to engage in physical activity while subjective norm not. Jeon and Cha (2019) found that intention can significantly affect fifth and sixth-grade children's health promotion behavior, and subjective norm and perceived behavioral control can significantly affect the health promotion intention while attitude can not.…”
Section: The Theory Of Planed Behaviormentioning
confidence: 98%
“…Wang and Wang (2015) found that intention has a significant effect on children's (ages 9 to 13) physical activity, attitude and perceived behavioral control have a significant effect on intention to engage in physical activity while subjective norm not. Jeon and Cha (2019) found that intention can significantly affect fifth and sixth-grade children's health promotion behavior, and subjective norm and perceived behavioral control can significantly affect the health promotion intention while attitude can not.…”
Section: The Theory Of Planed Behaviormentioning
confidence: 98%